Enhanced expression of human ABC-transporter tap is associated with cellular resistance to mitoxantrone - Lage, Hermann; Schadendorf, Dirk (FEBS letters, 2001)
Multidrug resistance (MDR) phenotypes have been associated with the overexpression of various members of the superfamily of ATP binding cassette (ABC) transporters. Here we demonstrate that a member of the ABC-transporter family, the heterodimer ‘transporter associated with antigen processing’ (TAP), physiologically involved in major histocompatibility complex class I-restricted antigen presentation, is significantly overexpressed in the human gastric carcinoma cell line EPG85-257RNOV exhibiting a mitoxantrone-resistant phenotype. This tumor cell line shows an atypical MDR phenotype in the absence of ‘P-glycoprotein’ or ‘MDR-associated protein’ overexpression but with an enforced ‘breast cancer resistance protein’ expression level. Transfection of both TAP subunits encoding cDNA molecules, TAP1 and TAP2, into the drug-sensitive parental gastric carcinoma cell line EPG85-257P conferred a 3.3-fold resistance to mitoxantrone but not to alternative anti-neoplastic agents. Furthermore, cell clones transfected with both, but not singularly expressed TAP1 or TAP2, reduced cellular mitoxantrone accumulation. Taken together, the data suggest that the heterodimeric TAP complex possesses characteristics of a xenobiotic transporter and that the TAP dimer contributes to the atypical MDR phenotype of human cancer cells.